Endocannabinoid Regulation of Learned Fear Inhibition - Warren, William George (2023)
Post-traumatic stress disorder and other anxiety-related disorders are characterised by impaired extinction and symptom relapse. Preclinical research into fear and extinction learning provides a translatable model for clinical settings. The endocannabinoid system is involved in extinction learning. However, research regarding endocannabinoid metabolism inhibition in extinction impairment and fear relapse is lacking. Spontaneous fear recovery, the return of learned fear over time after successful extinction, models fear relapse. Immediate extinction following fear conditioning impairs later extinction recall. Male Lister Hooded rats underwent Pavlovian fear conditioning in paradigms of spontaneous fear recovery or immediate extinction. The endocannabinoid metabolism inhibitors, URB597 or JZL184 (which increase the levels of anandamide and 2-arachidonoylglycerol, respectively) were administered intraperitoneally before or after extinction training depending on the paradigm. A positive control experiment used the b-adrenergic receptor antagonist, propranolol, in the immediate extinction paradigm. Neither URB597 nor JZL184 prevented fear relapse, nor did they rescue extinction impairments. A high dose of JZL184 acutely impaired immediate extinction acquisition. Propranolol acutely reduced baseline freezing prior to extinction training, facilitated immediate extinction acquisition, but did not rescue extinction impairment. These results suggest that endocannabinoid metabolism inhibition may not affect fear relapse and extinction impairment within the current paradigms. However, factors such as drug timing (e.g., when treatment occurred in relation to behavioural training or testing) and rat characteristics (e.g., strain, sex, and age) may have affected the results. Future research should address these potential confounds to assess the potential benefit of endocannabinoid metabolism inhibition in fear relapse and impaired extinction.